Effectiveness of Continuous Nursing Care on Quality of Life and Management of Complications in Patients with Ostomy Surgery: A Systematic Review - I Made Dwi Budhiasa Ari Serengga; Luh Gede Wirani Riskayanti Darmawan; Lisa Isdaryanti; Dwi Puji Lestari; Kiki Fajar Nurhidayah; Abu Bakar (GLOBAL HEALTH SCIENCE GROUP, 2025)
Individuals undergoing ostomy surgery frequently encounter various physical, emotional, and social challenges that may adversely affect their quality of life. Continuous Nursing Care (CNC) has been recognized for its potential in strengthening self-care skills and decreasing the incidence of postoperative complications. This review seeks to evaluate the influence of CNC on enhancing life quality and addressing complications among individuals with an ostomy. Objective to determine the effectiveness of Continuous Nursing Care (CNC) in improving quality of life and managing complications among patients undergoing ostomy surgery. This systematic review was conducted in accordance with the PRISMA 2020 guidelines. A comprehensive literature search was performed for studies published between 2019 and 2023, utilizing Boolean operators and MeSH terms: (